الكلمات الأجنبيّة في العامية الجزائرية المُتداولة ـ دراسة تطبيقيّة ـ - بن يطو محمد الغزالي (Université de M'sila, 2020)
الملخص : كانت الجزائر طوال تاريخها الحافل بالأحداث محلّ أطماع كثير من الأعداء والشعوب المتوسطية خاصة ،وظلّ هؤلاء الأقوام قرونا من الزمن جاثمين على صدور الجزائريين ،ولا شكّ من خلال طول إقامتهم بالجزائر تركوا بصماتهم الثقافية والعسكرية والعمرانيّة على أرضنا ، و من الآثار التي بقيت شاهدة على ذلك إلى الآن بعض ما تبقى من ألفاظهم اللغويّة التي تماهت في العامية الجزائريّة المستعملة اليوم ، وهذا ما شدّ انتباهي إليه ودفعني إلى البحث عن بقايا تلك الملفوظات اللغويّة المترسّبة في عاميتنا المتداولة ، وحوّلت ذلك إلى ورقة بحث استقري الموضوع وألاحق بعضها لمعرفة اللغة التي تنتسب إليها ، ولذا توخى عملي منهجا تطبيقيا أكثر يتتبّع الوقائع اللغويّة في صورتها الاجتماعيّة البحتة ، وتستند في مرجعيتها إلى ما ألتقطه من أقوال و ممارسات لغوية أكثر ممّا تستند إلى مراجع علميّة أكاديميّة باستثناء بعض المعاجم والقواميس الأجنبيّة التي تقتضيها الضرورة العلمية . summary Algeria was throughout its history, the eventful replaced coverts a lot of enemies and peoples of the Mediterranean special, and these nations centuries of time perched on the issuance of the Algerians, no doubt through the length of their stay in Algeria, they left their mark in cultural, military and construction on our land, and of the effects which remained a witness to it. to now some remains of the language which was in vernacular Algerian used today, and that's what caught my eye to him and pushed me to search for the remains of those vocabularies language translator in slang we traded, and turned this into a research paper the topic I'm chasing some learn the language to which they belong, So be a practical approach practical The linguistic facts are more closely followed in their purely social form, and their reference is based more on statements and language practices than on academic scientific references, with the exception of some foreign dictionaries and dictionaries as required by scientific necessity . .
Keywords: الثقافة ، العمران، التمازج ،اللفظ المتداول ،تداخل الثقافات ، التركية ، الاسبانية ، الفارسية ، الفرنسية ، العبرية